Semipermeable lipid bilayers exhibit diastereoselectivity favoring ribose - Sacerdote, M. G. (National Academy of Sciences, 2005)
Nutrient uptake by a primitive cell would have been limited by the permeability characteristics of its membrane. We measured the permeabilities of model protocellular membranes to water, five of the six pentoses, and selected aldohexoses, ketohexoses, and three to six carbon alditols by following volume changes of vesicles after the addition of solute to the external medium. Solute hydrophobicities correlated poorly with permeability coefficients within one structural class of compounds. The permeability coefficients of diastereomeric sugars differed by as much as a factor of 10, with ribose being the most permeable aldopentose. Flexible alditols and sugars, sugars biased toward or restricted to furanose forms, and sugars having anomers with hydrophobic faces permeated more quickly than compounds lacking these features. Among the aldopentoses, only ribose possesses all of these properties. Ribose permeated both fatty acid and phospholipid membranes more rapidly than the other aldopentoses or hexoses. The enhanced permeability conferred by the unique conformational preferences of ribose would have allowed faster assimilation of ribose by primitive cells as they passively absorbed materials from the environment. The kinetic advantage of ribose over the other aldopentoses in crossing membranes may therefore have been one factor that facilitated the emergence of the RNA world.